“Prevalencia de toxoplasma gondii en alumnas de la carrera de psicología clínica de la Universidad Nacional de Chimborazo” - Valeria Lissette, Llerena Cano (2017)
A descriptive – transversal study was done to determine the seroprevalence of Toxoplasma gondii in student women of the Clinical Psychology career at the National University of Chimborazo, in March – August 2017, in the order to determine the level of knowledge associated with risk factors as: Main routes of transmission, hygiene habits, contact with animals, forms of infection and correlate the results achieved which were got through the application of a survey and the development of the enzyme linked enzyme of the inmmunosorbent to Toxoplasma gondii. The data were processed through the statistical program Microsoft Excel and their results were evaluated in percentages and units of measures established by the HUMAN technique. Coming to conclusions that the level of knowledge is very low because the elements that were referred are not very significant about this pathology, with an average seroprevalence of seropositivity in correspondence with the sample studied, unlike the existing correlation with risk factors identified there in; It is stablished as recommendations the strict strengthening to the compliance of the controls to the mothers in gestation stage and programs on this disease in a way nthat is affordable from the economic point of view.